Online-Based Information System For Short Semester At Information System Study Program With PHP My SQL - Fakhri Ardiansyah; Indra Kanedi; Herlina Latipa Sari (Jurnal Media Computer Science, 2022)
Improvement of grades is a lecture process carried out in a short time outside the regular schedule which is intended to provide opportunities for students to improve their poor grades. In this era of globalization, it is very important that the need for accurate, precise and fast information in presenting very complete data is one of the important goals. For this reason, computers play an active role in all fields, especially in the Information System study program and computers make information will make things easier. The internet is a series or network of interconnected computers which comes from the word interconnected networking. Internet is a global network that connects a network with other networks around the world.